Linking the yield stress functionality of polyglycerol polyricinoleate in a highly filled suspension to its molecular properties. (1st August 2022) - Price, Ruth; Gray, David; Watson, Nicholas; Vieira, Josélio; Wolf, Bettina
Abstract: Polyglycerol polyricinoleate (PGPR) is a food emulsifier with a unique yield stress reducing efficacy in fat-based suspensions. There are many commercially available PGPRs, and the different products vary in their impact on the yield stress. Choosing the right PGPR for a specific formulation is often based on empirical data and the experience of the formulator. Lack of fundamental understanding of why these differences exist hampers reformulation efforts to replace PGPR. Therefore, this study aimed to link the yield stress reducing efficacy of PGPR to its molecular properties. Five commercial PGPR samples were studied (3 g/kg) in a concentrated suspension of icing sugar (650 g/kg, ≈ 530 mL/L) in sunflower oil (with naturally-occurring surface-active molecules removed). Rheological analysis revealed Herschel-Bulkley yield stress variations of between 0.90 ± 0.06 Pa and 1.90 ± 0.18 Pa, compared to 57.6 ± 15.8 Pa in the absence of PGPR. Yield stress was correlated to critical micelle concentration, obtained from oil-water interfacial tension data. Applying molecular characterisation techniques revealed that the presence of a hydroxyl group on the fatty acid at the end of the polyricinoleate estolide chain could be linked to inferior yield stress reducing efficacy. Highlights: Commercial polyglycerol polyricinoleates imparted different yield stress reduction. Critical micelle concentration correlated to yield stress. Molecular weight range of commercial samples showed no variation. Least efficient PGPR had a higher proportion of hydroxyl groups at the estolide end.